Evaluación de tres híbridos de sandía (citrulluslanatusschrad) sometidos a diferentes distanciamientos de siembra. época seca 2013. - Alarcón Zambrano, Manuel Enrique (2014)
This research was conducted between the months of August to November 2013 on the campus of the ESPAM MFL. Lemon In site, parish Sock Region Bolivar province of Manabi, geographically located at 0 ° 49'23 South Latitude and 80 ° 11'01 west longitude at an altitude of 15 m /; it aimed to potentiate the cultivation of watermelon in the valley of the Rio Carrizal, evaluating various hybrids under different planting distances. Block Design was used Completely Randomized (DBCA) in a factorial arrangement A x B + 1 with three replicates, the study variables were, fruit length, fruit diameter, bark thickness, average fruit weight, number of useful fruits per plot, number of fruits per plant, brix, number of fruit per hectare yield in kilograms per hectare. Furthermore, the additional variables; days to emergence, days to flowering, days to harvest, fruit rind color, flesh color. The results and their statistical analysis determined that the best average weight of fruits per plant was the hybrid ORION with 5.33 kg, while the Glorys Jumbo won the largest number of fruits per plant 1.48, and the highest yield with 15701.17 kg / ha. From the economic point of view the M1D1 treatment (M1 = Glorys Jumbo, D1 = 0.70 mx 4.00 m) resulted the best alternative for having the highest marginal rate of return 183.77% due to variation in the cost of each treatment.